Phenylphosphonic acid modified MOF-based solid-state electrolyte, method of making and use thereof

CN122931009APending Publication Date: 2026-10-16WUHAN INST OF TECH +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407161.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有技术中,很多固态电解质均添加了金属有机框架,但常规金属有机框架材料极性位点单一,与离子液体、无机快离子导体复配后界面作用弱

Benefits of technology

[0014] This invention employs an EDC/NHS activation system to covalently graft phenylphosphonic acid onto the surface of amino-functionalized UIO-66, thereby modifying the functional groups of MOF materials. This modification method enriches the polar sites on the material surface, effectively improving the interfacial compatibility between the modified MOF and inorganic fast ion conductors and ionic liquid electrolytes, constructing a continuous and stable lithium-ion transport channel, and significantly enhancing the ionic conductivity and structural stability of the solid electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931009A_ABST
    Figure CN122931009A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solid electrolytes, in particular to a phenyl phosphonic acid modified MOF-based solid electrolyte and a preparation method and application thereof. The solid electrolyte comprises an ionic liquid electrolyte, an inorganic fast ion conductor and UIO-66-PPA; the UIO-66-PPA is obtained by covalently grafting phenyl phosphonic acid on the amino group of UIO-66-NH2. In the application, the phenyl phosphonic acid is covalently grafted to the surface of the amino-functionalized UIO-66, the MOF material is modified by a functional group, the material surface polarity sites are enriched, the interface compatibility between the modified MOF, the inorganic fast ion conductor and the ionic liquid electrolyte is effectively improved, a continuous and stable lithium ion transmission channel is constructed, the ionic conductivity and the structural stability of the solid electrolyte are significantly improved, and excellent rate performance and long cycle stability are exhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, and in particular to a phenylphosphonic acid modified MOF-based solid electrolyte, its preparation method, and its application. Background Technology

[0002] Currently, solid electrolytes are mainly classified into three major systems: polymer-based, inorganic ceramic-based, and composite-based. Polymer solid electrolytes have good flexibility, but low ionic conductivity at room temperature and poor thermal stability. Pure inorganic ceramic electrolytes have excellent ionic conductivity, but they are brittle, difficult to process, have insufficient contact with the electrode interface, and have high interfacial impedance. Although existing composite electrolytes combine some advantages of the two types of materials, they still have defects such as poor component compatibility, weak lithium dendrite suppression, and easy interface degradation after long-term cycling, making it difficult to achieve a balance between high ionic conductivity, low interfacial impedance, and long-term cycling stability.

[0003] Metal-organic frameworks (MOFs) possess high specific surface area, tunable pore structure, and abundant functional groups, making them promising candidates for solid-state electrolytes. While many existing solid-state electrolytes incorporate MOFs, conventional MOF materials exhibit limited polarity and weak interfacial interactions when combined with ionic liquids and inorganic fast ion conductors. Summary of the Invention

[0004] The purpose of this invention is to address the aforementioned shortcomings of the prior art by proposing a phenylphosphonic acid-modified MOF-based solid electrolyte, its preparation method, and its applications.

[0005] The primary objective of this invention is to provide a phenylphosphonic acid-modified MOF-based solid electrolyte, comprising an ionic liquid electrolyte, an inorganic fast ion conductor, and UIO-66-PPA, wherein the mass-to-volume ratio of the inorganic fast ion conductor and UIO-66-PPA to the ionic liquid electrolyte is 200 mg : 150-250 μL; and the mass ratio of the inorganic fast ion conductor to UIO-66-PPA is 2-3 : 2-3. The UIO-66-PPA is a phenylphosphonic acid covalently grafted onto the amino group of UIO-66-NH2; The preparation method of UIO-66-PPA is as follows: S1. Dissolve phenylphosphonic acid, EDC and NHS in anhydrous DMF to obtain an activation solution; S2. Disperse UIO-66-NH2 powder in anhydrous DMF to obtain a dispersion; S3. Add the above-mentioned activating solution to the dispersion and stir the reaction at 40-60 °C. After the reaction is completed, centrifuge, wash and dry to obtain phenylphosphonic acid modified UIO-66-NH2, i.e., UIO-66-PPA.

[0006] Furthermore, in step S1, the molar ratio of phenylphosphonic acid, EDC, and NHS is 1:1-2:1-2, and the concentration of phenylphosphonic acid in the activation solution is 0.15 mol / L.

[0007] Furthermore, in step S2, the solid-liquid ratio in the dispersion is 1g : 20-40 mL.

[0008] Furthermore, in step S3, the volume ratio of the activating liquid to the dispersion liquid is 1:1.

[0009] Furthermore, in step S3, the reaction is stirred at 40-60 °C for 4-8 h.

[0010] Furthermore, the ionic liquid electrolyte is a lithium salt dissolved in an ionic liquid, with a lithium salt concentration of 0.8-1.2 mol / L. The lithium salt is lithium bis(trifluoromethanesulfonyl)imide, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and the inorganic fast ion conductor is Li3InCl6.

[0011] Furthermore, using zirconium tetrachloride and 2-aminoterephthalic acid as raw materials, acetic acid and concentrated hydrochloric acid as regulators, and N,N-dimethylformamide as an organic solvent, UiO-66-NH2 material was synthesized by a solvothermal method.

[0012] A second objective of this invention is to provide a method for preparing the phenylphosphonic acid-modified MOF-based solid electrolyte as described above, comprising the following steps: Preparation of UIO-66-PPA; Lithium salts are dissolved in ionic liquids to obtain ionic liquid electrolytes; The inorganic fast ion conductor and UIO-66-PPA are mixed and ground evenly according to the mass-volume ratio, and then added to the ionic liquid electrolyte. The grinding and mixing are continued until a uniform soft mud-like paste is formed, which is the solid electrolyte.

[0013] A third objective of the present invention is to provide a lithium iron phosphate-lithium metal solid-state battery, comprising a lithium iron phosphate positive electrode, a lithium metal negative electrode, and a phenylphosphonic acid modified MOF-based solid electrolyte disposed between the two, as described above.

[0014] This invention employs an EDC / NHS activation system to covalently graft phenylphosphonic acid onto the surface of amino-functionalized UIO-66, thereby modifying the functional groups of MOF materials. This modification method enriches the polar sites on the material surface, effectively improving the interfacial compatibility between the modified MOF and inorganic fast ion conductors and ionic liquid electrolytes, constructing a continuous and stable lithium-ion transport channel, and significantly enhancing the ionic conductivity and structural stability of the solid electrolyte.

[0015] This invention combines UIO-66-PPA, Li3InCl6 (an inorganic fast ion conductor), and a lithium salt / ionic liquid electrolyte to prepare a mud-like solid electrolyte. This solid electrolyte possesses excellent flexibility and plasticity, allowing it to tightly adhere to the electrode surface, significantly reducing the interfacial contact resistance between the electrolyte and the positive and negative electrodes. It also integrates the high ionic conductivity of inorganic materials with the excellent interfacial wettability of ionic liquids, resulting in overall performance far superior to traditional single-type solid electrolytes. Furthermore, this solid electrolyte effectively inhibits the growth of lithium dendrites on the surface of the lithium metal anode, reducing electrode side reactions. When combined with a lithium iron phosphate cathode, the resulting solid-state battery exhibits excellent rate performance and long-cycle stability, significantly improving overall safety. Attached Figure Description

[0016] Figure 1 SEM image of UIO-66-NH2 prepared in Example 1; Figure 2 SEM image of UIO-66-PPA prepared in Example 1; Figure 3 SEM image of the UPP prepared in Example 1; Figure 4 XRD patterns of UIO-66-NH2, UIO-66-PPA, and UPP prepared in Example 1; Figure 5 FTIR spectra of UIO-66-NH2 and UIO-66-PPA prepared in Example 1; Figure 6 The graphs show the first and 100th charge-discharge cycles of the solid-state battery prepared in Example 1. Figure 7 The discharge performance curves of the solid-state battery prepared in Example 1 at different rates are shown. Figure 8 The graph shows the capacity change of the solid-state battery prepared in Example 1 at a 1C rate over a long cycle. Detailed Implementation

[0017] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.

[0018] Example 1 1. Preparation of amino-functionalized MOF material UIO-66-NH2 Prepare materials using a molar ratio of ZrCl4:2-aminoterephthalic acid:acetic acid:concentrated hydrochloric acid:DMF = 1:0.8:80:2:400. Dissolve zirconium tetrachloride and 2-aminoterephthalic acid in DMF, then add acetic acid and concentrated hydrochloric acid sequentially and stir until homogeneous. Transfer the solution to a reaction vessel and react at a constant temperature of 110℃ for 24 h. After natural cooling, wash three times alternately with DMF and anhydrous ethanol, and dry at 100℃ for 18 h to obtain UIO-66-NH2 powder.

[0019] 2. Preparation of UIO-66-PPA by modification of phenylphosphonic acid The molar ratio of phenylphosphonic acid:EDC:NHS:anhydrous DMF was 1:1.2:1.2:1.2. The mixture was stirred and activated at 20℃ for 1 h to obtain the activated solution.

[0020] 1 g of UIO-66-NH2 was dispersed in 30 mL of anhydrous DMF to obtain a dispersion. 30 mL of activation solution was added, and the mixture was stirred at 50 °C for 6 h. After centrifugation, the mixture was washed three times each with DMF and methanol, and then dried under vacuum to obtain UIO-66-PPA.

[0021] 3. Preparation of solid electrolyte UPP (1) Preparation of ionic liquid electrolyte: LiTFSI is dissolved in ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (EMIM TFSI) at a concentration of 1.0 mol / L.

[0022] (2) By mass: 650 parts of Li3InCl and 50 parts of UIO-66-PPA, grind and mix evenly to obtain a mixed powder.

[0023] (3) 200 mg of the mixed powder in step (2) is added to 200 μL of the ionic liquid electrolyte prepared in step (1) and ground thoroughly until a uniform soft mud paste is formed to obtain phenylphosphonic acid modified MOF-based solid electrolyte UPP.

[0024] 4. Solid-state battery assembly Lithium iron phosphate cathode sheets were vacuum dried at 70℃ for 10 h; lithium metal sheets were cut and the oxide layer was removed for later use.

[0025] The UPP was coated onto the positive electrode surface with a thickness of 100 micrometers using a scraper. The coating was left to stand at room temperature for 20 minutes, leaving a 1.5 mm blank area at the edge.

[0026] The cathode-UPP-lithium anode stack was aligned and centered, and a pressure of 0.35 MPa was applied and held for 5 min. Solid-state batteries were then fabricated using aluminum-plastic film heat sealing at a temperature of 155℃, a pressure of 0.45 MPa, and a single-sided sealing time of 3 s.

[0027] Example 2 The overall process parameters were the same as in Example 1, except that the molar ratio ZrCl4:2-aminoterephthalic acid:acetic acid:concentrated hydrochloric acid:DMF was adjusted to 1:0.6:60:1:300, the reaction temperature was 100℃, and the reaction time was 12 h. After washing, the product was dried at 80℃ for 12 h to obtain UIO-66-NH2.

[0028] Other process parameters are the same as in Example 1.

[0029] Example 3 The overall process parameters are the same as in Example 1, only the raw material ratio for UIO-66-PPA preparation is adjusted: Phenylated phosphonic acid:EDC:NHS:anhydrous DMF=1:2:2:2, activated at 30℃ for 2 h.

[0030] UIO-66-NH2 was dispersed in anhydrous DMF at a solid-liquid ratio of 1g:40mL and reacted at 60℃ for 8h. The post-treatment was the same as in Example 1.

[0031] Other process parameters are the same as in Example 1.

[0032] Example 4 The overall process parameters are the same as in Example 1, only the ratio of the composite powder is adjusted: 645 samples of Li3InCl and 55 samples of UIO-66-PPA.

[0033] The remaining MOF synthesis, modification, electrolyte concentration, and battery assembly parameters were consistent with those in Example 1.

[0034] Example 5 The overall process parameters are the same as in Example 1, only the ratio of the composite powder is adjusted: 655 samples of Li3InCl and 45 samples of UIO-66-PPA.

[0035] The remaining MOF synthesis, modification, electrolyte concentration, and battery assembly parameters were consistent with those in Example 1.

[0036] Comparative Example 1 (UIO-66-NH2 was used directly without phenylphosphonic acid modification) UIO-66-NH2 powder prepared in Example 1 was used directly to replace phenylphosphonic acid to prepare UIO-66-PPA for solid electrolyte preparation.

[0037] The entire process and parameters for solid-state battery assembly are consistent with those in Example 1.

[0038] Comparative Example 2 (without adding inorganic fast ion conductor Li3InCl6) 1. The preparation process and parameters of UIO-66-NH2 and UIO-66-PPA are exactly the same as those in Example 1.

[0039] 2. Preparation of solid electrolyte: Only 100 parts of UIO-66-PPA powder were used, and Li3InCl6 was not added; other process parameters were the same as in Example 1.

[0040] 3. All process parameters for solid-state battery assembly are consistent with those in Example 1.

[0041] Comparative Example 3 (pure solid-phase composite electrolyte without the addition of ionic liquid electrolyte) 1. The preparation process and parameters of UIO-66-NH2 and UIO-66-PPA are exactly the same as those in Example 1.

[0042] 2. Powder ratio: 650 parts Li3InCl and 50 parts UIO-66-PPA are thoroughly ground and mixed without adding any ionic liquid electrolyte to obtain pure solid powder electrolyte.

[0043] 3. The powder is pressed into thin sheets by dry pressing and then assembled into batteries. The electrode pretreatment, stacking, pressurization and packaging parameters are the same as in Example 1.

[0044] This section uses the solid electrolyte UPP prepared in Example 1 and the corresponding lithium iron phosphate-lithium metal solid battery as test samples to carry out electrochemical performance tests at room temperature. The test equipment used is the Blue Battery Test System.

[0045] Figure 1 The image shows a SEM image of UIO-66-NH2 prepared in Example 1. As can be seen from the SEM image of UIO-66-NH2, the amino-functionalized MOF material exhibits a regular octahedral grain morphology with uniform particle size distribution, clear grain outline, smooth surface, and no obvious agglomeration or structural collapse. This indicates that the solvothermal synthesis process conditions used in this invention are suitable, and a UIO-66-NH2 precursor material with good crystal morphology and complete structure has been successfully prepared.

[0046] Figure 2 The image shows a SEM image of UIO-66-PPA prepared in Example 1. As can be seen from the image, the UIO-66-PPA obtained after phenylphosphonic acid grafting modification still retains the typical octahedral framework structure of the UIO series MOFs, and the main crystal morphology remains intact, proving that the covalent grafting modification process does not destroy the original crystal structure of the MOF. Compared to before modification, the surface of the material particles becomes rougher, with a fine coating layer appearing, directly confirming that phenylphosphonic acid has been successfully loaded onto the surface of the UIO-66-NH2 particles, demonstrating a significant modification effect.

[0047] Figure 3 The image shows a SEM image of the UPP prepared in Example 1. The solid electrolyte UPP is composed of a modified MOF, a Li3InCl6 inorganic fast ion conductor, and an ionic liquid. The SEM image shows that the various components are interwoven and tightly bonded, resulting in a dense overall structure. The interparticle voids are fully filled by the ionic liquid, forming a continuous composite network structure. This structure effectively increases the contact area between components, which is beneficial for constructing continuous lithium-ion transport channels and improving the interfacial adhesion between the electrolyte and the electrode.

[0048] Figure 4 The XRD patterns of UIO-66-NH2, UIO-66-PPA, and UPP prepared in Example 1 are shown in the figures. As can be seen from the figures, the characteristic diffraction peak positions of UIO-66-NH2 and UIO-66-PPA are basically consistent, with sharp peak shapes and matching standard simulated patterns. This indicates that the phenylphosphonic acid modification only occurs at the functional group level on the material surface and does not change the bulk crystal structure of the MOF, thus the crystallinity of the material remains unaffected. The spectrum of the UPP composite electrolyte retains the characteristic diffraction peaks of both the modified MOF and Li3InCl6, with no obvious impurity peaks generated, proving that the chemical properties of each composite component are stable, no side reactions occur, and the system has good compatibility.

[0049] Figure 5 The FTIR spectra of UIO-66-NH2 and UIO-66-PPA prepared in Example 1 were compared. The Fourier transform infrared spectra of the two materials showed that UIO-66-NH2 exhibited a characteristic amino absorption peak at the corresponding wavenumber. In the spectrum of the modified UIO-66-PPA, the intensity of the original amino absorption peak was weakened, and a significant PO bond characteristic absorption peak appeared. This confirmed that phenylphosphonic acid was successfully grafted onto the amino site of UIO-66-NH2 through chemical bonding, thus completing the modification of the target functional group.

[0050] Test Example 1: Charge and Discharge Performance Test The solid-state batteries prepared in Examples 1-5 and Comparative Examples 1-3 were placed at room temperature, and the test voltage range was set to 2.5–3.8 V. Constant current charge-discharge tests were performed at a current rate of 1 C. The initial charge-discharge curve and the 100th charge-discharge cycle curve were recorded. The test data are as follows: Figure 6 As shown in Table 1.

[0051] Figure 6 The graphs shown are the first and 100th charge-discharge cycles of the solid-state battery prepared in Example 1. Figure 6It is evident that the solid-state battery based on UPP solid electrolyte exhibits regular charge-discharge curves with minimal polarization at the first and 100th cycles, and a stable and highly overlapping charge-discharge plateau. The battery achieves an initial discharge specific capacity of 162 mAh / g, and after 100 cycles, the discharge specific capacity remains at 128 mAh / g, demonstrating extremely low capacity decay. This superior charge-discharge performance stems from the innovative design of the phenylphosphonic acid covalently grafted modified MOF of this invention. This invention utilizes an EDC / NHS activation system to achieve phenylphosphonic acid graft modification, introducing PO polar functional groups without disrupting the original crystal structure of the MOF. This not only improves the interfacial compatibility between the modified MOF and inorganic fast ion conductors and ionic liquids but also constructs a continuous, low-resistance lithium-ion transport channel, effectively enhancing the electrolyte's ionic conductivity and ensuring the battery achieves a high initial discharge capacity. Simultaneously, the abundant functional groups and stable interfacial structure after modification slow down the rate of interfacial degradation during cycling. Therefore, the battery can maintain a high discharge capacity even after 100 cycles, effectively suppressing capacity decay.

[0052] Table 1

[0053] The five sets of samples from this invention exhibited excellent overall performance with minimal fluctuations. The initial discharge specific capacity of all samples exceeded 155 mAh / g, and the coulombic efficiency after 100 cycles was consistently above 96%. The formulation in Example 1 was the optimal ratio, demonstrating the best ion transport efficiency and interface adhesion, and exhibiting the best initial capacity and cycle retention among all samples. After adjusting the parameters within the defined range, no significant performance degradation was observed in the batteries, proving that the formulation and process parameters of this invention have a wide range of adaptability and strong process stability.

[0054] The comparative examples showed that the performance of all three groups was significantly worse than that of the examples, confirming the necessity of the components and modification process of this invention. Comparative Example 1: Using unmodified UIO-66-NH2 directly resulted in a material with a single functional group on its surface, poor system compatibility, and imperfect ion transport channels. The initial capacity decreased significantly, and the interface continued to deteriorate during long-term cycling, with a capacity retention rate of only 82.2% after 100 cycles.

[0055] Comparative Example 2: Without the addition of inorganic fast ion conductors, the lithium-ion conductivity of the electrolyte is significantly weakened, battery polarization is aggravated, and the initial capacity and cycle stability are further reduced, with a capacity retention rate of only 74.7%.

[0056] Comparative Example 3: Without the addition of an ionic liquid electrolyte, the electrolyte lacked flexibility and interfacial wettability, resulting in severely poor contact between the electrode and the electrolyte and extremely high interfacial impedance. The initial discharge capacity of the battery was significantly lower than expected, and the defects continued to expand during cycling. After 100 cycles, the capacity retention rate was only 45.0%, indicating that the battery was essentially unusable.

[0057] The synergistic effect of phenylphosphonic acid-modified MOF, inorganic fast ion conductor, and ionic liquid electrolyte is key to ensuring the high ionic conductivity and low interfacial impedance of the solid electrolyte. The solid electrolyte and solid battery prepared by this invention combine high initial capacity with excellent long-term cycle stability, and their overall electrochemical performance is far superior to existing single-system and unmodified material systems.

[0058] Test Example 2: Ratio Performance Test At room temperature, different charge and discharge rates were set sequentially at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, and 5 C. Each rate was cycled 5 times, and the discharge specific capacity corresponding to different rates was recorded to evaluate the rate adaptability of solid-state batteries.

[0059] Depend on Figure 7 As can be seen, the solid-state battery assembled in Example 1 of this invention possesses excellent rate performance. At a low rate of 0.1 C, the battery exhibits the highest discharge specific capacity. As the rate gradually increases to 1 C, 2 C, and even 5 C, the battery maintains a high discharge specific capacity, demonstrating excellent capacity retention at high rates. This characteristic benefits from the innovative synergistic architecture of the modified MOF, inorganic fast ion conductor, and ionic liquid ternary composite system of this invention. This invention creatively combines three types of functional materials: Li3InCl6, an inorganic fast ion conductor, endows the system with intrinsically high lithium-ion conductivity, meeting the requirements for rapid ion migration under high current; UIO-66-PPA, relying on its porous structure and functional groups, uniformly regulates lithium-ion flux, avoiding local ion enrichment at high rates; and the ionic liquid enables the electrolyte to form a mud-like structure, possessing good flexibility and interfacial wettability, significantly reducing interfacial impedance. The complementary advantages and synergistic effects of these three materials allow the battery to operate stably across a wide rate range.

[0060] Test Example 3 Cyclic Stability Test Test methods Under room temperature conditions, with a fixed charge / discharge rate of 1 C and a voltage range of 2.5–3.8 V, the battery was subjected to a long-cycle test, totaling 100 cycles. The discharge specific capacity of each cycle was recorded in real time to analyze the battery's long-cycle life and capacity decay characteristics.

[0061] Depend on Figure 8It can be seen that the solid-state battery using UPP solid electrolyte has a coulombic efficiency of over 96% after 100 cycles at 1 C rate, and the capacity curve is flat during the cycle with no rapid decay. At the same time, the electrolyte layer can effectively suppress the growth of lithium dendrites on the surface of the lithium metal anode, and no abnormal problems such as short circuits or bulging occurred throughout the battery cycle.

[0062] The composite electrolyte of this invention forms a dual protection mechanism: on the one hand, the modified MOF and Li3InCl6 intertwine to form a dense, rigid network, physically preventing lithium dendrite penetration; on the other hand, the diverse polar functional groups on the material surface can regulate the uniform deposition of lithium ions, chemically inhibiting lithium dendrite initiation, while simultaneously stabilizing the solid-solid interface and reducing side reactions such as electrolyte decomposition. The entire material system is chemically stable, with no adverse side reactions between components, and its structure and performance are not easily degraded during long-term cycling.

[0063] Test Example 4: Room Temperature Ionic Conductivity Test The solid electrolytes prepared in Examples 1-5 and Comparative Examples 1-3 were pressed into uniformly thick discs, and stainless steel blocking electrodes (SS|Ele|SS) were attached to both sides to assemble test cells. Electrochemical impedance spectroscopy (EIS) tests were performed at 25 °C using an electrochemical workstation, with a test frequency range of 1×10⁻⁶. -2 Hz~1×10 6 Hz. Obtain the electrolyte bulk phase resistance R, and calculate the room temperature ionic conductivity according to the following formula: Where σ is the ionic conductivity (S / cm), L is the electrolyte thickness (cm), A is the effective contact area of ​​the electrode (cm²), and R is the electrolyte bulk resistance (Ω).

[0064] For any points not covered above, existing technologies shall apply.

[0065] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A phenylphosphonic acid-modified MOF-based solid electrolyte, characterized in that, It includes an ionic liquid electrolyte, an inorganic fast ion conductor, and UIO-66-PPA. The mass-to-volume ratio of the inorganic fast ion conductor and UIO-66-PPA to the ionic liquid electrolyte is 200 mg : 150-250 μL; the mass ratio of the inorganic fast ion conductor to UIO-66-PPA is 2-3 : 2-3. The UIO-66-PPA is a phenylphosphonic acid covalently grafted onto the amino group of UIO-66-NH2; The preparation method of UIO-66-PPA is as follows: S1. Dissolve phenylphosphonic acid, EDC and NHS in anhydrous DMF to obtain an activation solution; S2. Disperse UIO-66-NH2 powder in anhydrous DMF to obtain a dispersion; S3. Add the above-mentioned activating solution to the dispersion and stir the reaction at 40-60 °C. After the reaction is completed, centrifuge, wash and dry to obtain phenylphosphonic acid modified UIO-66-NH2, i.e., UIO-66-PPA.

2. The phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, In step S1, the molar ratio of phenylphosphonic acid, EDC, and NHS is 1:1-2:1-2, and the concentration of phenylphosphonic acid in the activation solution is 0.15 mol / L.

3. The phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, In step S2, the solid-liquid ratio in the dispersion is 1g : 20-40 mL.

4. The phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, In step S3, the volume ratio of the activating solution to the dispersion solution is 1:

1.

5. The phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, In step S3, the reaction is stirred at 40-60 °C for 4-8 h.

6. The phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, The ionic liquid electrolyte consists of a lithium salt dissolved in an ionic liquid with a concentration of 0.8-1.2 mol / L. The lithium salt is lithium bis(trifluoromethanesulfonyl)imide, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and the inorganic fast ion conductor is Li3InCl6.

7. A phenylphosphonic acid-modified MOF-based solid electrolyte as described in claim 1, characterized in that, UiO-66-NH2 material was synthesized by a solvothermal method using zirconium tetrachloride and 2-aminoterephthalic acid as raw materials, acetic acid and concentrated hydrochloric acid as regulators, and N,N-dimethylformamide as an organic solvent.

8. A method for preparing a phenylphosphonic acid-modified MOF-based solid electrolyte as described in any one of claims 1-7, characterized in that, Includes the following steps: Preparation of UIO-66-PPA; Lithium salts are dissolved in ionic liquids to obtain ionic liquid electrolytes; The inorganic fast ion conductor and UIO-66-PPA are mixed and ground evenly according to the mass-volume ratio, and then added to the ionic liquid electrolyte. The grinding and mixing are continued until a uniform soft mud-like paste is formed, which is the solid electrolyte.

9. A lithium iron phosphate-lithium metal solid-state battery, characterized in that, It includes a lithium iron phosphate cathode, a lithium metal anode, and a phenylphosphonic acid modified MOF-based solid electrolyte as described in any one of claims 1-7 disposed between the two.